France in the Vienna System of International Relations (the First Half of The 19th Century) - I. V. Ignatchenko (Vestnik MGIMO-Universiteta)
Abstract: The Vienna system of international relations established at the Congress of Vienna in 1814-1815, was a real challenge for the French political elite during all subsequent decades. France was a defeated party and was thus morally humiliated. The objective for all French governments after 1815 was to improve the position of France in this new system of international relations, including due to the destabilization and breaking of the Vienna system. In the years of the Restoration in France (1814-1830) a major foreign policy action of the government of Louis XVIII was the intervention in Spain in 1823, which refers to the Spanish revolution of 1820-1823. The French government, reflecting the interests of the European reaction, had hoped to raise these military prestige of France, and consequently to raise the question of the revision of the treatises of Vienna of 1815. Despite the success of the intervention, she has not brought the big political dividends in France. After the July revolution 1830 in France, the foreign policy of France intensified. Leading French politicians defined quite clearly exclusive spheres of influence of France, and in 1832 the French troops invaded Central Italy, capturing the city of Ancona. In 1840, during the second Oriental crisis, the French government has opposed themselves to the rest of Europe for the first time since the Napoleonic wars. Ultimately, the strategic position of France in the middle East was weakened. But the exacerbation of international conflict contributed to the strengthening of the French army and Navy. Further successes of the French diplomacy will be linked to the period of the Second Empire in France, in particular, with the Crimean war, that raised has raised status of France, and the decision of the Italian question in the second half of the 60-ies of the XIX century.